Dual polarized engineering the extinction cross-section of a dielectric wire using graphene-based oligomers - Shiva Hayati Raad (Nature Portfolio, 2021)
Abstract In this paper, graphene-coated spherical nanoparticles are arranged around an infinite length dielectric cylinder to enhance its extinction cross-section. Initially, a single longitudinal one-dimensional periodic array is considered in different loci concerning the transverse electric (TE) incident plane wave. It is observed that regardless of the position of the particles, the extinction cross-section of the dielectric cylinder is considerably enhanced with respect to the bare one. Later, by increasing the number of longitudinal plasmonic arrays around the cylinder, each residing in a different azimuthal direction, the extinction cross-section is further manipulated to observe double pronounced Fano resonances. The origin of the Fano resonances is described by considering their planar counterparts constructed by the periodic assembly of plasmonic oligomers. Finally, the hexamer configuration is considered as the prototype, and the effect of various optical, geometrical, and material parameters on the optical response is investigated in detail. Interestingly, due to the spherical symmetry of the cells, the extinction cross-section is also enhanced for the transverse magnetic (TM) incident wave, which is unattainable using a continuous plasmonic cover made of metal or graphene. The potential application of our proposed structure is in the design of reconfigurable conformal optical absorbers and sensors.